Press Marketing in Times of COVID-19: Comparison of Native and Digital Press Consumption Patterns - Crespo Pereira, Verónica (2021)
The exceptional situation that has caused COVID-19 has had consequences in the press around the world. Confinement has replaced the habit of reading the paper press for the digital version. This situation allows many questions to be asked about the future of print runs and the type of post-pandemic information consumption. In this sense, an approximate investigation has been carried out, framed in the field of Ecuador, with the aim of identifying behavior patterns of consumers of informational products through digital editions that allow to determine the bases of a new access model and consumption of this type of media which, in the socio-geographical space studied, is still in an initial phase of transformation, a question that constitutes one of the main contributions of the research; Therefore, the sensitivity of countries such as Ecuador to the incidence of health crises or natural disasters cannot be ignored where access to information is essential. The investigation has been carried out at the most critical moment of the pandemic, as it represents a turning point in the inflection of the habitual consumption of newspapers. The evolution of relevant indicators for digital businessmodels such as the engagement of 17 Ecuadorian newspapers during the pre-pandemicmonths (February) and confinement (March to May) has been analyzed.